Sosialisasi Penerapan Standar Audit Laporan Keuangan Badan Layanan Umum Daerah (BLUD) Puskesmas Se-Kabupaten Bone - Masnawaty Sangkala; Andi Faisal (ARRUS Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to enhance the understanding of financial managers at Regional Public Service Agency (BLUD) Community Health Centers (Puskesmas) in Bone Regency regarding external audit procedures and standards applicable to BLUD financial statements. The background problem is the limited understanding among most puskesmas financial managers concerning external audit mechanisms and requirements as stipulated in BLUD financial management regulations. The activity was conducted as a socialization event using lecture, interactive discussion, and question-and-answer methods, attended by 20 participants representing 14 BLUD Puskesmas across Bone Regency, held at Puskesmas Ulaweng, Tellu Limpoe District, Bone Regency, in April 2026. Evaluation was conducted using pre-test and post-test instruments to measure improvements in participants' understanding. Results showed an average pre-test score of 55.0 and an average post-test score of 83.5, reflecting an improvement of 28.5 points. This improvement indicates that the socialization activity was effective in transferring knowledge regarding BLUD external audit standards and procedures. This activity is expected to contribute to improved accountability and transparency in BLUD puskesmas financial management in Bone Regency.